David Copperfield [compact disc, unabridged] - Dickens, Charles. 1812-1870 (Tantor Audio, 2009)
Charles Dickens' 1850 classic epic, David Copperfield, unfolds the story of David, an optimistic and hard-working lad who's orphaned in his youth. Raised initially by his brutal stepfather, who halts David's schooling and sends him to work in a factory, David eventually finds a home with his eccentric, but kind aunt, Betsey. Later in life, David trains for a career in law, but eventually becomes a writer.